Functional consequences of phenotypic variation between locally adapted populations: Swimming performance and ventilation in extremophile fish. (8th February 2020) - Camarillo, Henry; Arias Rodriguez, Lenin; Tobler, Michael
Abstract: Natural selection drives the evolution of traits to optimize organismal performance, but optimization of one aspect of performance can influence other aspects of performance. Here, we asked how phenotypic variation between locally adapted fish populations affects locomotion and ventilation, testing for functional trade‐offs and trait–performance correlations. Specifically, we investigated two populations of livebearing fish ( Poecilia mexicana ) that inhabit distinct habitat types (hydrogen‐sulphide‐rich springs and adjacent nonsulphidic streams). For each individual, we quantified different metrics of burst swimming during simulated predator attacks, steady swimming and gill ventilation. Coinciding with predictions, we documented significant population differences in all aspects of performance, with fish from sulphidic habitats exhibiting higher steady swimming performance and higher ventilation capacity, but slower burst swimming. There was a significant functional trade‐off between steady and burst swimming, but not between different aspects of locomotion and ventilation. Although our findings about population differences in locomotion performance largely parallel the results from previous studies, we provide novel insights about how morphological variation might impact ventilation and ultimately oxygen acquisition. Overall, our analyses provided insights into the functional consequences of previously documented phenotypic variation, which will help to disentangle the effects of different sources of selection that may coincide along complex environmental gradients. Abstract : Divergence of body shape during local adaptation to different environments impacts locomotion and ventilation in fishes.